Pengaruh Brand Equity, Kepedulian Merek dan Personalitas Brand Terhadap Loyalitas Pelanggan Melalui Kepuasan Konsumen Sebagai Variabel Intervening: Studi pada Konsumen Kopi Kenangan Sidoarjo - Ariiq Elmo Lavansa; Nurul Azizah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine and analyze the influence of brand equity in the Kopi Kenangan brand on customer loyalty. The method used in this research uses a qualitative method which uses an approach that collects, analyzes and interprets data in the form of numbers or measurable data. With the findings that have been investigated through the process starting from the data collection stage, the data processing process, until reaching the data analysis stage, researchers can conclude that brand equity partially has an insignificant and positive influence on loyalty.